Ilexsaponin A1 Ameliorates Diet-Induced Nonalcoholic Fatty Liver Disease by Regulating Bile Acid Metabolism in Mice - Wen-wen Zhao; Wen-wen Zhao; Meng Xiao; Meng Xiao; Xia Wu; Xiu-wei Li; Xiao-xi Li; Ting Zhao; Lan Yu; Xiao-qing Chen (Frontiers Media S.A., 2021)
Bile acid (BA) metabolism is an attractive therapeutic target in nonalcoholic fatty liver disease (NAFLD). We aimed to investigate the effect of ilexsaponin A1 (IsA), a major bioactive ingredient of Ilex, on high-fat diet (HFD)-induced NAFLD in mice with a focus on BA homeostasis. Male C57BL/6J mice were fed an HFD to induce NAFLD and were treated with IsA (120 mg/kg) for 8 weeks. The results showed that administration of IsA significantly decreased serum total cholesterol (TC), attenuated liver steatosis, and decreased total hepatic BA levels in HFD-induced NAFLD mice. IsA-treated mice showed increased BA synthesis in the alternative pathway by upregulating the gene expression levels of sterol 27-hydroxylase (CYP27A1) and cholesterol 7b-hydroxylase (CYP7B1). IsA treatment accelerated efflux and decreased uptake of BA in liver by increasing hepatic farnesoid X receptor (FXR) and bile salt export pump (BSEP) expression, and reducing Na+-taurocholic acid cotransporting polypeptide (NTCP) expression. Alterations in the gut microbiota and increased bile salt hydrolase (BSH) activity might be related to enhanced fecal BA excretion in IsA-treated mice. This study demonstrates that consumption of IsA may prevent HFD-induced NAFLD and exert cholesterol-lowering effects, possibly by regulating the gut microbiota and BA metabolism.